'We Just Call Them People': Positive Regard as a Dimension of Culture in Group Homes for People with Severe Intellectual Disability. Issue 4 (1st October 2014) - Bigby, Christine; Knox, Marie; Beadle‐Brown, Julie; Clement, Tim
<x xml:space="preserve">Abstract</x> Background A dimension of the culture in group homes is staff regard for residents. In underperforming group homes, staff regard residents as being not 'like us' (Bigby, Knox, Beadle‐Brown, Clement & Mansell, 2012). We hypothesized the opposite pole of this dimension, in higher performing group homes, would be that staff regard residents positively. Method Three in‐depth qualitative case studies were conducted in higher performing group homes using participant observation, interviews and document review. Results Consistent pattern of staff practices and talk, as well as artefacts, demonstrated staff had a positive regard for residents, who were seen as being 'like us'. Explicit and continuing attention was given to sustaining positive regard for residents in everyday staff practices and to turning abstract values into concrete realities. Conclusions This positive cultural norm was established, operationalized and embedded through structures, such as a formal policy about language, and processes such as peer monitoring and practice leadership.